1992
DOI: 10.1093/oxfordjournals.humrep.a137631
|View full text |Cite
|
Sign up to set email alerts
|

CASE REPORT: Transcervical tubal cannulation and falloposcopy for the management of tubal pregnancy*

Abstract: This is the first report of transcervical salpingoscopic visualization of tubal pregnancy in two patients. The falloposcope was introduced through a catheter used routinely for transcervical tubal cannulation, guided by tactile impression. We have previously demonstrated that it is possible to diagnose and treat tubal pregnancies via a transcervical intra-Fallopian cannula. Falloposcopy could help select appropriate patients for transcervical intra-Fallopian therapy by verifying the site of implantation and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 0 publications
0
5
0
3
Order By: Relevance
“…Initial studies in the field of small diameter laparoscopy concentrated on evaluating diagnostic accuracy of the small diameter laparoscopes, but their studies were hampered by instruments that produced low levels of light, reduced fields of view, and generally poor resolution Dorsey and Tabb et al, Risqué et al 7,8 Later, with the development in fiberoptic technology, the optical performance of microlaparoscopes was shown to be comparable with conventional laparoscopes (O Bauer et al). 9 Two other prospective studies on a series of 20 patients Molly D et al and 52 patients Haeusler et al concluded that the accuracy of microlaparoscope is comparable to that with the conventional 10mm laparoscope.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial studies in the field of small diameter laparoscopy concentrated on evaluating diagnostic accuracy of the small diameter laparoscopes, but their studies were hampered by instruments that produced low levels of light, reduced fields of view, and generally poor resolution Dorsey and Tabb et al, Risqué et al 7,8 Later, with the development in fiberoptic technology, the optical performance of microlaparoscopes was shown to be comparable with conventional laparoscopes (O Bauer et al). 9 Two other prospective studies on a series of 20 patients Molly D et al and 52 patients Haeusler et al concluded that the accuracy of microlaparoscope is comparable to that with the conventional 10mm laparoscope.…”
Section: Discussionmentioning
confidence: 99%
“…4,7 Further these instruments have many advantages over larger ones such as anaesthesia requirements, less postoperative discomfort, 8 decreased risk of adhesion formation and reduced risk of incisional hernias. [7][8][9][10][11] To the best of our knowledge, this is the only largest prospective randomized comparative study comparing various parameters in diagnostic laparoscopy of infertility patients using 5 mm and 2.9 mm minilaparoscopes. The concept of small is beautiful is more justified when it comes to laparoscopy in evaluation of patients of infertility.…”
Section: Introductionmentioning
confidence: 99%
“…Local injection of MTX has also been performed under laparoscopic control and by transvaginal puncture, with good results [3,8,[11][12][13][14][15]. New modes of local MTX treatment have been reported, either via transcervical tubal cannulation [16,17] or via hysteroscopy [18].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective case-control study revealed the following results for laparoscopic GIFT versus ultrasoundguided transvaginal GIFT: clinical pregnancy rate 35.0% versus 20.0% and ongoing pregnancy rate 23.3% versus 10.0%. 15 Other potential indications for tubal catheterization include diagnosis and treatment of tubal pregnancy, 16 and tubal sterilization. 17,18 Both of these techniques are in the experimental stages.…”
Section: Indicationsmentioning
confidence: 99%